A review on classification, types, and properties of humidity sensors / Nurhana Ilmira Harun …[et al.] - Harun, Nurhana Ilmira; Sheikh Abdul Aziz, Siti Sumaiyah; Salleh, Nunshaimah; Senawi, Syamsir Akmal; Hashim, Azhan; Ali, Abdul Malik Marwan; Yahya, Muhd Zu Azhan (2014)
The development of humidity sensors have been studied due to their significant effects on quality of life, quality of products, safety, cost, and health. This present work had been concerned with humidity sensor, which emphasized on the classifications, types, and properties of the sensor. Humidity sensors are classified into electrolyte humidity sensor, ceramic humidity sensor, semiconductor-type humidity sensor, and polymer film humidity sensor. Two categories of humidity sensors were identified, which were capacitive- and resistive-types. Furthermore, this study focused on the properties of humidity sensors in order to satisfy the widest range of applications, including high sensitivity, high accuracy, good linearity, large operating range of humidity and temperature, short response time, good reproducibility, small hysteresis, good durability and long life, high resistance against contaminants, negligible temperature dependence, and low fabrication cost.